Patient journey in erosive oesophagitis: real-world perspectives from US physicians and patients. Issue 1 (22nd July 2022) - Vaezi, Michael F; Brunton, Stephen; Mark Fendrick, A; Howden, Colin W; Atkinson, Christian; Pelletier, Corey; Jacob, Rinu; Spechler, Stuart J
Abstract : Objective: Management of erosive oesophagitis (EE) remains suboptimal, with many patients experiencing incomplete healing, ongoing symptoms, and relapse despite proton pump inhibitor (PPI) treatment. The Study of Acid-Related Disorders investigated patient burden of individuals with EE in a real-world setting. Design: US gastroenterologists (GIs) or family physicians (FPs)/general practitioners (GPs) treating patients with EE completed a physician survey and enrolled up to four patients with EE for a patient survey, with prespecified data extracted from medical records. Results: 102 GIs and 149 FPs/GPs completed the survey; data were available for 73 patients (mean age at diagnosis, 45.4 years). Omeprazole was healthcare professional (HCP)-preferred first-line treatment (60.8% GIs; 56.4% FPs/GPs), and pantoprazole preferred second line (29.4% and 32.9%, respectively). Price and insurance coverage (both 55.5% HCPs) and familiarity (47.9%) key drivers for omeprazole; insurance coverage (52.0%), price (50.0%), familiarity (48.0%), initial symptom relief (46.0%), and safety (44.0%) key drivers for pantoprazole. Only 49.3% patients took medication as instructed all the time; 56.8% independently increased medication frequency some of the time. Despite treatment, 57.5% patients experienced heartburn and 30.1% regurgitation; heartburn was the most bothersome symptom. 58.9% patients believed that their symptoms could be better controlled; only 28.3% HCPs were very satisfied with current treatment options. 83.6% patients wanted long-lasting treatment options. Fast symptom relief for patients was a top priority for 66.1% HCPs, while 56.6% would welcome alternatives to PPIs. Conclusion: This real-world multicentre study highlights the need for new, rapidly acting treatments in EE that reduce symptom burden, offer durable healing and provide symptom control.